Design Of Sugar Cane Ujice Evaporator With Spray-Cyclone A New Breakthrough In Sugar Industry - Immawan, Taufiq; Muflihat, Syakia (Archives of Business Research, 2018)
In the sugar industry, the problems that occur not only in the factory but also in sugar cane land, namely a decrease in factory load because the age of the developing factory needs maintenance and replacement of the machine that must be adjusted. Therefore, it is necessary to make a breakthrough to maximize operations from land to factories. The breakthrough was made in the form of making a mobile evaporator that can support the business process of reengineering the production of sugar cane juice on the land. In addition, the problem encountered in the functional evaporator itself is the steam pressure setting that is not in accordance with the SOP, the results of brix are difficult to predict, cleaning of hard sugar juice catchers, cleaning of difficult heating bodies and too long evaporation process. The problem- solving process is conduct using the TRIZ method to get design specifications that are expected by the user. Improving and worsening contradiction matrix in the form of 3 attributes that are used, namely an effective process, easier temperature settings, and portable. The results from TRIZ provide several specific solutions for functional tools such as adopting the sugar juice input method into the heating body using spray and cyclone to create a more effective process, adding additional blowers to maintain heating temperature and evaporator dimensions that are suitable for mobile application. The solution obtained from TRIZ was applied in the manufacture of evaporators and experiments on these devices to produce sugarcane juice that meets quality standards. The initial volume of this experiment was 15 liters of sugar cane juice and the final volume was 7 liters. The initial Brix sugar cane juice is 23% and the final brix is 40%